2020
DOI: 10.1021/acs.bioconjchem.0c00564
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Corona Conundrum: Exploring the Advantages and Drawbacks of its Presence around Amphiphilic Nanoparticles

Abstract: The success of targeted drug delivery systems still requires a detailed understanding about the biological consequences of self-developed biomolecular coronas around them, since this is the surface that interacts with living cells. Herein, we report the behavior of carbohydrate-decorated amphiphilic nanoparticles in a plasma environment with regard to the formation and biological consequences of the protein corona. Naked amphiphilic nanoparticles were produced through the self-assembly of azido-PEO 900 -docosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Moreover, protein corona formation causes destabilization of the nanoparticles due to agglomeration of the particles, causing deleterious effects in the treatment regimen. [ 44 ] As a result. the stability of the nanoparticle system was also measured in a solution containing 10% human serum at 37 °C to mimic physiological blood conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, protein corona formation causes destabilization of the nanoparticles due to agglomeration of the particles, causing deleterious effects in the treatment regimen. [ 44 ] As a result. the stability of the nanoparticle system was also measured in a solution containing 10% human serum at 37 °C to mimic physiological blood conditions.…”
Section: Resultsmentioning
confidence: 97%
“…The hydrodynamic radius was measured using dynamic light scattering for a period of 7 days while the nanoparticles were in storage conditions of 4°C; as seen in the graph in Figure 2D, we observe that the size and zeta potential is constant over 7 days with minimal fluctuation hence proving that the nanoparticles are indeed stable. During systemic circulation, studies have shown that nanoparticle destabilization may occur due to the adsorption of serum proteins on the surface of the nanoparticle system, termed as the protein corona effect 34 . To test out the stability of the MSNPs in physiological conditions, the nanoparticles were incubated in PBS with 10% human serum for 24 h, while their hydrodynamic size and surface charge (zeta potential) were measured at regular intervals.…”
Section: Resultsmentioning
confidence: 99%
“…During systemic circulation, studies have shown that nanoparticle destabilization may occur due to the adsorption of serum proteins on the surface of the nanoparticle system, termed as the protein corona effect. 34 To test out the stability of the MSNPs in physiological conditions, the nanoparticles were incubated in PBS with 10% human serum for 24 h, while their hydrodynamic size and surface charge (zeta potential) were measured at regular intervals. As seen in Figure 2E, the nanoparticle system is indeed stable in human serum, hence proving that it can be used in physiological conditions.…”
Section: Synthesis and Characterization Of Msnpsmentioning
confidence: 99%
“…Nanoparticles administered into the blood can interact nonspecifically with serum proteins and form a shell of protein, called the protein corona [39][40][41][42][43][44]. Protein corona formation is mainly mediated by coulombic and Van der Waals forces, hydrogen bonding, and hydrophobic interactions [45].…”
Section: Modulating Interactions Between Nps and Proteinsmentioning
confidence: 99%